Local government administration and the challenges of development in Nigeria within the provisions of the 1999 constitution (2012)
Rural and grassroots development is the concern of every responsible and responsive government in any political System. This is because political participation in the development process has continued to elude the people at the grassroots. Development remains insignificant if it does not positively affect the lives of those in the periphery of decision making arrangement. The Nigerian state therefore created local governments as the third tier of government with the objective of ensuring effective, measurable and efficient Service delivery to the people. There is no gainsaying that local government administration in Nigeria is faced with numerous challenges. This paper will dwell majorly on these challenges and illuminate the factors responsible for them. To this end, this paper will rely on descriptive approach and well structured suggestions. It will identify the multifarious nature of problems and challenges facing local government administration, as well as proffer adequate and practical Solutions to them in order to evolve viable and development oriented third tier of government